1993
DOI: 10.2165/00003088-199325020-00008
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of Ibuprofen in Patients with Liver Cirrhosis

Abstract: Following a single oral dose of racemic ibuprofen 600mg the stereoselective disposition of its enantiomers was studied in 8 patients with moderate to severe cirrhosis. Compared with the elimination half-life (t1/2) of (-)-R- and (+)-S-ibuprofen in 8 healthy age-matched controls (1.7 +/- 0.3h and 1.8 +/- 0.5h, respectively), t1/2 was prolonged significantly (p < 0.045 and < 0.001, respectively) in patients with cirrhosis (t1/2 = 3.1 +/- 1.7h and 3.4 +/- 1.0h, respectively). Whereas the low amounts excreted unch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…reported to be independent of the dose of racemic ibuprofen [37]. This consistency of the reported values of F i in healthy volunteers justi®es its use from the literature, unless data originate from subjects with liver disease where inversion is impaired [21], or when subjects were treated with clo®brate that increases the inversion of R-to S-ibuprofen [23]. The model presented here may also be used when direct information on S-ibuprofen pharmacokinetics is available from concomitant administration of labelled S-ibuprofen, making it possible directly to estimate F i rather than incorporating a value from the literature.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…reported to be independent of the dose of racemic ibuprofen [37]. This consistency of the reported values of F i in healthy volunteers justi®es its use from the literature, unless data originate from subjects with liver disease where inversion is impaired [21], or when subjects were treated with clo®brate that increases the inversion of R-to S-ibuprofen [23]. The model presented here may also be used when direct information on S-ibuprofen pharmacokinetics is available from concomitant administration of labelled S-ibuprofen, making it possible directly to estimate F i rather than incorporating a value from the literature.…”
Section: Discussionsupporting
confidence: 61%
“…A fraction F i of the clearance of R-ibuprofen consists of inversion clearance of R-to S-ibuprofen, CL R, inv . The inversion was assigned to the central compartments what is compatible with the fact that most of the inversion takes place in the liver [20] while other sites play a minor role [21,22]. The fraction F i was set to 0.6 as reported from a previous study in a comparable study population [23].…”
Section: Discussionmentioning
confidence: 99%
“…ibuprofen with evidence of reduced metabolic inversion of the R(-) to S(?) enantiomer (Li et al 1993). Alcoholic liver disease also prolongs the T max for the total Cp as well as the t 1/2 (Albert and Gernaat 1984).…”
Section: Pharmacokinetics In Adultsmentioning
confidence: 99%
“…Results from previous studies have showed that the (S)/(R) AUC ratio varies in different pathological conditions. The reported values for renal failure [8] and liver cirrhosis [17] were 2.1 and 0.91, respectively, which may be accounted for by the roles of liver and kidney in the disposition of ibuprofen enantiomers (Figure 2). …”
Section: Discussionmentioning
confidence: 98%